Implementasi Metode Rivest Shamir Adleman untuk Enkripsi dan Dekripsi Text - Fatonah; Dadang Iskandar Mulyana (E-Jurnal Universitas Samudra, 2022)
Abstract Until now information technology is developing rapidly, resulting in a lot of information that is easily stolen because of increasingly sophisticated technology. For this reason, a program is needed to secure the confidentiality of information so that it is not easily read. Cryptography is one of the solutions developed to maintain the confidentiality of the information. In cryptography, there is a process where the information sent will be encoded which can be called encryption, then returned to the original information called decryption. Many techniques are owned by cryptography, one of which is a technique that has security that is difficult to solve, namely the RSA algorithm. In its application, the RSA cryptography method will create a program that can encrypt and decrypt text, and it is necessary to pay attention to the selection of prime numbers and the key generation process so that there is no attack on the RSA cryptography algorithm. The purpose of this is to ensure that the information sent reaches the recipient safely. Other people will find it difficult to read the information sent because it uses a code that is difficult to crack. Keywords: RSA, Cryptography, Encryption, Decryption, Text